«We were united by a desire to study the family…» - Burova, Svetlana N.; Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2026)
The interview is dedicated to the anniversary of renowned Belarusian sociologist, PhD in law, docent S. N. Burova. She reflects on her life, the role of sociology in society, and her transition to sociology, citing the example of her teacher, N. G. Yurkevich, her research projects, the academic school of family sociology, her teachers and colleagues, discusses the challenges sociologists face, shares her experiences, and offers advice to young people pursuing a career in sociology. The conversation touches on the challenges of modern sociological science, the methodology and methods of sociology, interdisciplinarity in the study of new challenges and threats, and examines the characteristics and key requirements of contemporary research. The discussion also touches on the development and promising directions of Russian family sociology and the improvement of sociologist education.